Mesoporous SiO2 Sphere-Based Electrochemical Impedance Immunosensor for Ultrasensitive Detection of Bovine Interferon-γ - Xia, Yanping; Chen, Hui; Liu, Ruixin; Shi, Feng; Ren, Chuanli; Li, Juan; Zhao, Jie; Chen, Xiang; Yang, Zhanjun (Journal of analysis and testing, 2023)
Interferon-γ is a kind of protein with a wide range of biological activities, which can regulate the immune function of the body, and can be used as an important marker to detect and treat bovine tuberculosis diseases. Here, a picogram-level bovine interferon-γ (BoIFN-γ) electrochemical impedance immunosensor was constructed for the first time using mesoporous silica nanospheres (MSNs) to immobilize specific monoclonal BoIFN-γ antibodies. The MSNs and BoIFN-γ immunosensors were characterized using scanning electron microscopy, transmission electron microscope, nitrogen adsorption experiment, X-ray photoelectron spectra, and contact angle measurements. MSNs possess a substantial specific surface area and significant hydrophilicity, and can immobilize many antibody molecules, thereby improving detection sensitivity. The immunosensor has a linear detection range from 0.001 to 10.0 ng/mL with an exceptionally low detection limit of 0.62 pg/mL. Compared to the traditional BoIFN-γ analysis method, BoIFN-γ immunosensor presents superiorities in sensitivity, wide linear range as well as short processing time. More importantly, the BoIFN-γ sensor exhibits high selectivity, reliable repeatability as well as stability, providing a promising application prospect for the early diagnosis of Mycobacterium bovis infection.